The Study of Collaborative Structure of Pre-world Heritage Management; Case Study Chiang Mai, Thailand - Arkarapotiwong, Piyadech (Journal of Architectural/Planning Research and Studies (JARS), 2019)
The study of collaborative structure of pre-world heritage management, Chiang Mai, Thailand is very important, since the study result will help to manage the accurate and proper plan for Chiang Mai town’s characteristic. However, the management plan has the using of collaborative of stakeholders to be part of the process, which come up with the complexity in the process of analysis, which whether the trends of the management is appropriated with Chiang Mai, or not. This research aims to study the collaborative structure in the pre-world heritage management of Chiang Mai. It lays the idea’s frame of the research analysis on the social network analysis concept. This idea can analyze the solid management plan and reduce the complexity to understanding. The research demonstrated that the collaborative organizations, which joined in the management network of the pre-world heritage site of Chiang Mai, have prepared a diversity of organizations and the city resources. However, the collaborative process tends to aim at conserving the traditional communities to live with monuments, which actually is the concept of the living heritage approach, but in realities the urban physical of Chiang Mai has been changed considerably. The using of a classic conservation method, which monitoring the physical aspects first, seems to suit with the recent city situation. Then, when the urban physical is evaluated in a good condition. The living heritage approach can bring back to be a main concept of conservation in order to conserve both the urban physical and the traditional communities.